GOVERNMENT PUBLIC RELATIONS STRATEGY IN ENHANCING THE INSTITUTIONAL IMAGE OF THE HOUSE OF REPRESENTATIVES OF THE REPUBLIC OF INDONESIA - Putra, Tubagus Haikal Gilang Mandala; Sagita, Novie Indrawati; Centia, Selvi (Syntax Literate, 2026)
The institutional image of the House of Representatives of the Republic of Indonesia (DPR RI) is a crucial element of government administration, as it directly influences political legitimacy, the effectiveness of representative functions, and the quality of state–society relations. This study aims to examine the government public relations strategy of the DPR RI as an integral component of public communication governance in strengthening the image of the legislative institution. Using a descriptive qualitative approach, the research draws on field observations, in-depth interviews, document analysis, and literature review to explore how DPR RI Public Relations performs its strategic role in accordance with principles of public administration and government public relations standards. The findings indicate that the DPR RI’s communication strategy operates through four main instruments: digital communication, public information disclosure services through the Information and Documentation Management Officer (PPID), public education programs, and media relations. These instruments are implemented using the RACE (Research, Action, Communication, Evaluation) model as an operational framework for planning, executing, and evaluating public communication. Furthermore, the strategy reflects the Dynamic Government paradigm, particularly in terms of thinking ahead, thinking across, thinking again, and digital adaptation, emphasizing institutional adaptability, cross-unit coordination, and organizational learning. However, the study also identifies persistent challenges, including limited human resources, underdeveloped communication standard operating procedures, and high exposure to negative media coverage. Therefore, strengthening governance-based public relations strategies, enhancing communication capacity, and modernizing the digital ecosystem are essential to building a more credible, accountable, and sustainable institutional image of the DPR RI.